Processing and performance of carbon/epoxy multi-scale composites containing carbon nanofibres and single walled carbon nanotubes - Rana, S. (2013)
The present paper reports and compares the processing and various properties of carbon/epoxy multi-scale composites developed incorporating vapor-grown carbon nanofibres (VCNFs) and single-walled carbon nanotubes (SWCNTs). CNFs and SWCNTs (0.5–1.5 wt. %) were dispersed within epoxy resin using a combination of ultrasonication and mechanical stirring in the presence of a non-ionic surfactant and the nanomaterial/resin dispersions were used to impregnate carbon fabrics in order to develop multi-scale composites. Various properties of multi-scale composites such as mechanical, dynamic mechanical, thermal transmission and wear performance were characterized and reported. It was observed from the experimental results that SWCNTs needed much longer dispersion treatment as compared to CNFs; however, the improvement in properties in case of CNT based multi-scale composites was also much higher. Incorporation of up to 1.5wt. % ofCNT within carbon/epoxy composites led to improvements of 46 % in elastic modulus, 9 % in tensile strength, 150 % in breaking strain, 170 % in toughness, 95 % in storage modulus (at 25 °C), 167 % in thermal conductivity and also significant improvements in the wear performance of composites. Additionally, a simplified modeling approach based on the micromechanical equations showed that the multi-scale composites, especially containing SWCNTs, presented elastic modulus very close to the predicted values.